Vaccination: the importance of herd immunity. Issue 1 (October 2007) - Doroshenko, Alexander; Halperin, Scott A
Herd immunity is an important concept for clinicians, public health professionals, epidemiologists, statisticians and policy makers. Herd immunity prevents the spread of infection in a community where immunization coverage is high, resulting in the burden of vaccine-preventable diseases being considerably reduced as a result of it. It is particularly relevant in evaluating the effectiveness of vaccination programs. This review examines the theory behind herd immunity and its historical role in disease eradication. Modern examples of the positive effects of herd immunity after the recent introduction of new vaccines are presented and herd-immunity limitations are outlined. Potential future applications of herd-immunity concepts are considered.